The Existence of Legal Aid Institutions in Providing Legal Aid Amidst COVID-19 Outbreak - Heru Pratama Adnan Amrullah (Universitas Negeri Semarang, 2021)
Corona Virus Disease 2019 (COVID 19) which hit Indonesia made a variety of legal cases that hit many parties like the case regarding the termination of employment relations unilaterally, protection against workers, the cancellation of cooperation contracts, the community accused of spreading the COVID 19 Virus until patients who were unable to pay medical expenses at the hospitality. To date, there have been no legal aid agencies that provide legal assistance on the various cases, even though they can be taken provide legal assistance, but also many things that affect legal assistance to be applied if legal assistance through the media and or legal assistance directly is carried out as constrains because of the existence of COVID 19 itself which makes all that must participate in handling COVID 19 namely be accepting social distances and other policies, reports of people who need very minimal legal assistance and the lack of information about legal assistance.